Effectiveness Hydroxyapatite from Chicken Eggshells for Adsorption of Chromium (VI) Metal Ion Electroplating Waste - Afifah Nur Ismawati; Ani Iryani; Linda Jati Kusumawadani (Helium: Journal of Science and Applied Chemistry, 2023)
The largest source of waste comes from household activities. One of the wastes that comes from household activities is chicken eggshells waste. Chicken eggshells contain 94% CaCO3 and can be used as a source of calcium to synthesize hydroxyapatite (Ca10(PO4)6(OH)2) by the precipitation method. Hydroxyapatite can be used as an adsorbent material because it has pores, inert, and wear-resistant so it can adsorb dissolved metal ions Cr (VI) contained in liquid waste from electroplating process. This research aims to synthesize hydroxyapatite from chicken eggshells and determine the optimum pH, contact time, adsorbent mass, and initial concentration of waste which influence the adsorption efficiency using continuous system column adsorption method with fixed flow rate 25 mL/min. In this study, the metal ions Cr (VI) was chosen as adsorbate because Cr (VI) is the main component in electroplating process. This research started from preparation of chicken eggshells waste then synthesized into hydroxyapatite and characterized using XRD, FTIR, and SEM that known structure formed adsorbent is hydroxyapatite and measuring the initial Cr (VI) concentration in waste using AAS with wavelength 357,9 nm. The result of optimizing are the optimum pH 5, contact time of 60 minutes, 3,5 gram of adsorbent mass, and the initial concentration of waste is 10 ppm. The analyzed were done for Cr (VI) concentration. The result showed 99,48% adsorption efficiency with final concentration of Cr (VI) is 0,07 ppm. The adsorption process followed the Freundlich isotherm model with maximum adsorption capacity of 3,93 mg/g hydroxyapatite.